PERAN TNI DALAM PENGAMANAN WILAYAH PERBATASAN DARAT GUNA MENDUKUNG KEUTUHAN WILAYAH NEGARA KESATUAN REPUBLIK INDONESIA (Studi Di Perbatasan Kalimantan Barat-Malaysia) - ANGGIT EXTON YUSTIAWAN,SH A.2021131038, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACThis thesis discusses the TNI role in securing land borders in order to support the territorial integrity of the Republic of Indonesia (Studies In West Kalimantan-Malaysia border). From the results of this thesis research we concluded that TNI's role in the Security Frontier Army To Support Territorial Integrity of the Unitary Republic of Indonesia Border West Kalimantan-Malaysia is not light because the border region are far away from the capital of the province and the capital of the State so often uncontrolled and neglected. The condition causes the border areas prone and vulnerable in terms of security, and the potential conflicts among States bordering if things are not handled wisely by the government. The role of the Army of Aspect Security and Defense, the military seeks to prevent and improve security and stability along the border areas of the island of Sebatik with troops of the Army Task Force Pamtas much as one company or 138 people, then to prevent border violations by both societies, military cooperation Army Malaysian (TDM) to patrol the border, in addition to preventing the smuggling of both people and goods as well as the possibility of a shift and making boundary markers is a strategic issue in the region TNI patrols and sweeping in every person and vehicle entering into this region in prevention against possible security threats and violations of sovereignty in the region. The role of the Army of Aspect Security and Defense, the military seeks to prevent and improve security and stability along the border areas of the island of Sebatik with troops of the Army Task Force Pamtas much as one company or 138 people, then to prevent border violations by both societies, military cooperation Army Malaysian (TDM) to patrol the border, in addition to preventing the smuggling of both people and goods as well as the possibility of a shift and making boundary markers is a strategic issue in the region TNI patrols and sweeping in every person and vehicle entering into this region in prevention against possible security threats and violations of sovereignty in the region. TNI's role in the Social Aspects, according to the TNI to foster a sense of unity to strengthen the sovereignty of the state is to do prevention by way of defending the region as an effective business. In this case the military attempted to approach the local community through social activities that work with government and community leaders which of these activities target directly touch on the interests of the people of this region through several program activities, namely, repairing damaged roads and hollow, constructing facilities worship and sanitation, education memyelenggarakan to defend the state, such as the health of mass treatment, and mass circumcision to communities far from health support facilities, where all this activity actually correlates directly in the creation of the durability of the wider region. In connection state does not always work in harmony for sure there are some potential problems that could destabilize relations between countries. Any problems that occur can cause two different impact for the country, these impacts can be either cooperation or conflict. Sometimes a conflict, one aspect affected by the conflict could spread to other aspects. To keep from happening or at least anticipate-konflk conflict that can occur, Indonesia should make efforts to resolve conflicts and improve the bargaining position (bargaining position). Any attempt aimed at that in the future there is no problem that interfere with cooperation among States which bersengketa.Pada essentially relations between countries influenced by the interests of each country and the relations between countries can work well if those interests do not clash. The border issue is an issue that is often a problem that is quite sensitive inter-state adjacent to each other. Relations between Indonesia and neighboring countries can actually be said to have been going pretty well, just how these countries respect each other and respect each other, to anticipate and manage potential conflicts, and ultimately develop bilateral cooperation of mutual benefit in various fields ( poleksosbud defense). Efforts that can be done for example by deterrence, Preventive Diplomacy and Cooperative Security.Keywords: Role of the Indonesian Armed Forces, In Security, the Frontier Army.